Analysis of Policy Implementation and Availability of Infrastructure on the Implementation of Early Breastfeeding Initiation After Cesarean Section Delivery in Private Hospitals in Kudus District - Lestari, Puji; Nugraheni, Sri Achadi; Sriatmi, Ayun (Jurnal Multidisiplin Madani, 2024)
Early initiation of breastfeeding (IMD) is placing the infant on the mother's chest or abdomen and allowing the infant to seek the mother's nipple within the first hour of birth. Caesarean section (SC) poses challenges to the implementation of Early Breastfeeding Initiation (IMD) in both internationally and nationally recommended hospital programs for maternal and infant care. The purpose of this study was to analyze policy implementation and analyze the availability of hospital facilities in the implementation of Early Breastfeeding Initiation (IMD) after Sectio Caesarean delivery. The research design was descriptive qualitative. The main informants of the study were SPOg doctors, implementing midwives and the Head of the Central Surgical Unit. Supporting informants are laboring mothers, central surgery unit nurses, pediatricians, hospital management. Data collection using in-depth interviews and observation. Data validity strategy using source triangulation. There is a policy contained in the decree of the hospital director and the hospital SOP as a work instruction for the implementing unit, monitoring is carried out every delivery and the division of tasks is carried out situationally. The number, competence and infrastructure are available well enough to support the implementation of IMD after Sectio Caesarea delivery in the hospital